ANALYSIS OF THE EFFECT OF TAX AVOIDANCE ON FIRM VALUE: SYSTEMATIC REVIEW - Idah Paridah; Hijroh Rokhayati (Jurnal Riset Akuntansi dan Keuangan, 2023)
This research aims to analyze and synthesize theory, research results, other explanatory variables and measurement of research variables about the effect of tax avoidance on firm value. This study uses the systematic literature review (SLR) method which examines 36 articles with a year of observation 2013-2020. The results of the study present theoretical mapping, research results, other explanatory variables, and measurements of research variables from literature sample. The most widely used theory is agency theory. The synthesis of the research results shows three classifications: tax avoidance has a significant positive effect, a significant negative and has no effect on firm value. Other dominant explanatory variables that also have a significant positive effect on firm value are profitability, firm size, capital structure, leverage and transparency. The synthesis of research variable measurements provides proxies and formulations for the operationalization of variables. The contribution of this research provides conceptual insights and managerial decisions.